2010
DOI: 10.1088/0953-4075/43/20/205203
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the dynamic screening on single-electron ionization of multi-electron atoms

Abstract: A complete formulation of the post-version of the continuum distorted wave-eikonal initial state model to investigate single-electron ionization of multi-electron atoms by fast bare ion beams is considered. The influence of the non-ionized electrons on the dynamic evolution of the ejected electron is analysed showing that the corresponding interaction plays a main role in the determination of double differential cross sections. It is demonstrated that its inclusion as an additional term in the perturbative pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 16 publications
5
44
0
Order By: Relevance
“…It can be explained in terms of the fact that the post version does not consider the inclusion of perturbative potentials which take into account the short range part of the electron dynamic screening. As a result the post version underestimates the results obtained with the prior approximation [46]. Also, it must be mentioned that the theoretical model does not take into account any inner-shell ionization process and some deviations could be seen in the higher-energy region 400-600 eV [see Figs.…”
Section: A Ddcs: Energy Distributionsmentioning
confidence: 98%
See 3 more Smart Citations
“…It can be explained in terms of the fact that the post version does not consider the inclusion of perturbative potentials which take into account the short range part of the electron dynamic screening. As a result the post version underestimates the results obtained with the prior approximation [46]. Also, it must be mentioned that the theoretical model does not take into account any inner-shell ionization process and some deviations could be seen in the higher-energy region 400-600 eV [see Figs.…”
Section: A Ddcs: Energy Distributionsmentioning
confidence: 98%
“…Therefore the results arising from the post version of the CDW-EIS model will differ from those obtained using the prior one. Recently Monti et al [46,47] have shown that the inclusion of this residual potential in the post version of the CDW-EIS model almost completely diminishes these post-prior discrepancies. Finally, the doubly differential cross section as a function of the emitted electron energy (E k ) and solid angle ( k ) is defined as…”
Section: Theoretical Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The discrepancies observed between the CDW-EIS results and the experimental data for electrons ejected with large energies at backward angles are a characteristic feature of the CDW-EIS model. In a recent publication 56 it has been described that, for atomic targets, the influence of the bound spectator electrons on the dynamic evolution of the ejected electron affects crucially the theoretical DDCSs (dynamic screening). The present CDW-EIS calculations take partially into account the dynamic screening through the effective target charge considered in the corresponding continuum factor of the exit channel.…”
Section: Iiia1 Ddcssmentioning
confidence: 99%